Introduction to Psychology The Full Noba Collection - Biswas-Diener, Robert; Diener, Ed; Open Textbook Library (Open Textbook Library, 2016)
This textbook represents the entire catalog of Noba topics. It contains 90 learning modules covering every area of psychology commonly taught in introductory courses. This book can be modified: feel free to rearrange or remove modules to better suit your specific needs.Please note that the publisher requires you to login to access and download the textbooks.
Psychology As Science -- Biological Basis of Behavior -- Sensation and Perception -- Development -- Cognition and Language -- Learning and Memory -- Social -- Personality -- Emotions and Motivation -- Psychological Disorders -- Well-Being
In English.
Description based on online resource
Keywords: Social sciences -- Textbooks; Psychology -- Textbooks